Educational guidelines for eating “fill my plate” for balanced nutrition in toddlers - Marina, Marina (Journal of Evidence-Based Community Health, 2024)
High-quality human resources (HR) are essential for organizations, including in managing balanced nutrition for young children. Nutrition education, specifically through the "Isi Piringku" Dietary Guidelines by the Indonesian Ministry of Health, aims to enhance public knowledge about balanced nutrition, which is crucial for child development. Although stunting prevalence has declined, rates remain high, especially in Maros Regency. This community service activity at Bontoa Health Center involved 21 mothers of young children, using interactive counseling methods. Evaluation results show improved understanding and engagement among mothers, expected to positively impact child nutrition quality